Colour in bivalve shells: Using resonance Raman spectroscopy to compare pigments at different phylogenetic levels - Wade,J; Pugh,H; Nightingale,J; Kim,J; Williams,ST (Journal of Raman Spectroscopy, 2019)
Several studies have suggested that shell colour may be phylogenetically distributed within the phylum Mollusca, but this pattern is confounded by our ignorance of the homology of colour and lack of understanding about the identity of most molluscan pigments. We use resonance Raman spectroscopy to address this problem by examining bivalve pigments producing a range of colours and compare spectra from taxa at different phylogenetic levels. The spectra of most shell pigments exhibited a skeletal signature typical of partially methylated polyenes, possibly modified carotenoids, with the strongest peaks occurring between 1,501–1,540 cm−1 and 1,117–1,144 cm−1 due to the CC (ν1) and C–C (ν2) stretching modes, respectively. Neither pigment class nor mineral structure differentiated Imparidentia and Pteriomorphia. Spectral acquisitions for purple pigments for two species of Asaphis suggest that identical or nearly identical pigments are shared within this genus, and some red pigments from distantly related species have similar spectra. Conversely, two species with brown shells have distinctly different pigments, highlighting the difficulty in determining the homology of colour even within a single class of pigments. Curiously, we were unable to detect any Raman activity for greencoloured shell or pigment peaks for the yellow area of Codakia paytenorum, suggesting that these colours are due to structural elements or a pigment that is quite different from those observed in other taxa examined to date. Our results are consistent with the idea that classes of pigments are evolutionarily ancient but heritable modifications may be specific to clades.